Plant-to-plant communication triggered by systemin primes anti-herbivore resistance in tomato. Issue 1 (December 2017) - Coppola, Mariangela; Cascone, Pasquale; Madonna, Valentina; Lelio, Ilaria; Esposito, Francesco; Avitabile, Concetta; Romanelli, Alessandra; Guerrieri, Emilio; Vitiello, Alessia; Pennacchio, Francesco; Rao, Rosa; Corrado, Giandomenico
Abstract Plants actively respond to herbivory by inducing various defense mechanisms in both damaged (locally) and non-damaged tissues (systemically). In addition, it is currently widely accepted that plant-to-plant communication allows specific neighbors to be warned of likely incoming stress (defense priming). Systemin is a plant peptide hormone promoting the systemic response to herbivory in tomato. This 18-aa peptide is also able to induce the release of bioactive Volatile Organic Compounds, thus also promoting the interaction between the tomato and the third trophic level (e.g. predators and parasitoids of insect pests). In this work, using a combination of gene expression (RNA-Seq and qRT-PCR), behavioral and chemical approaches, we demonstrate that systemin triggers metabolic changes of the plant that are capable of inducing a primed state in neighboring unchallenged plants. At the molecular level, the primed state is mainly associated with an elevated transcription of pattern -recognition receptors, signaling enzymes and transcription factors. Compared to naïve plants, systemin-primed plants were significantly more resistant to herbivorous pests, more attractive to parasitoids and showed an increased response to wounding. Small peptides are nowadays considered fundamental signaling molecules in many plant processes and this work extends the range of downstream effects of this class of molecules to intraspecific plant-to-plant communication.